Gestión administrativa y productividad laboral en el área de administración de la Municipalidad Distrital de San Juan Bautista, 2023 - Flores Jesus, Pablo Cesar (2024)
In 2023, the District Municipality of San Juan Bautista shows positive and sig nificant relationships between various organizational dimensions and the work performance of its employees. Administrative management, supported by a Pearson correlation of 0.776, stands out as a crucial factor, suggesting that effective administration has a positive impact on work performance. Addition ally, planning, organization, and direction show strong correlations, supporting the implementation of strategies to strengthen these areas to drive organiza tional success. Furthermore, the professional category is revealed as a rele vant element in the relationship between control and work performance, high lighting the importance of considering this factor in future strategies. These findings underscore the need for specific actions, such as training programs, improvements in processes, and organizational policies, to strengthen admin istrative effectiveness and enhance work performance in the municipal entity.